Pengaruh Model Pembelajaran Project Based Learning Terhadap Hasil Belajar Siswa Materi Sistem Pernapasan Manusia Pada Kelas V SD Pui Cicurug - Syafitri Novitasari; Mohammad Fahmi Nugraha; Yopa Taufik Saleh (PT. Hasba Edukasi Mandiri, 2026)
This research is driven by the low learning outcomes and conceptual understanding of fifth-grade students at SD PUI Cicurug regarding the human respiratory system, caused by the continued use of conventional teaching models. This study aims to determine the effect of the Project-Based Learning (PjBL) model on student learning outcomes in that subject matter. The research method employed is quantitative with a Quasi-Experimental Design, specifically the Non-equivalent Control Group Design. The population consisted of all 20 fifth-grade students at SD PUI Cicurug, selected using a Simple Random Sampling technique and divided into an experimental class (10 students) and a control class (10 students). Data collection techniques included observation, interviews, documentation, and validated objective test instruments. The results indicated a significant increase in the experimental class, with a post-test mean score of 91.5, substantially outperforming the control class, which achieved 78.5. Statistical analysis using the Paired Sample T-test yielded a significance value of 0.001 (p<0,05) leading to the rejection of the null hypothesis (H_o) and the acceptance of the alternative hypothesis (H_a) In conclusion, the application of the Project Based Learning (PJBL) model has a significant impact on improving student learning outcomes, where the creation of real projects bridges the gap between abstract science concepts and concrete, meaningful understanding.